2015
DOI: 10.2106/jbjs.n.00313
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Surgery for Lumbar Stenosis and Degenerative Spondylolisthesis in the Octogenarian Population

Abstract: Background: The purpose of this study was to determine whether surgery is an effective option for the treatment of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 20 publications
3
85
0
1
Order By: Relevance
“…The goal of conservative treatment is to reduce pain gradually over time; however, surgery is often recommended. The operative treatment for LSS and degenerative spondylolisthesis provides substantial lasting benefit compared with nonoperative care172327). As a result, the number of surgical procedures performed for LSS has increased steadily as the oldest sector of the population continues to grow1416).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of conservative treatment is to reduce pain gradually over time; however, surgery is often recommended. The operative treatment for LSS and degenerative spondylolisthesis provides substantial lasting benefit compared with nonoperative care172327). As a result, the number of surgical procedures performed for LSS has increased steadily as the oldest sector of the population continues to grow1416).…”
Section: Introductionmentioning
confidence: 99%
“…LSS is the most frequent indication for spinal surgery in elderly adults, and as the oldest segment of the population continues to grow, the prevalence is likely to increase . In individuals aged 80 and older, favorable outcomes after surgery for LSS were reported in 25 participants from an observational study and 58 participants from a subgroup analysis of the Spine Patient Outcomes Research Trial . Still, knowledge about outcomes after surgery for LSS in individuals aged 80 and older is limited.…”
mentioning
confidence: 99%
“…[10][11][12] In individuals aged 80 and older, favorable outcomes after surgery for LSS were reported in 25 participants from an observational study 13 and 58 participants from a subgroup analysis of the Spine Patient Outcomes Research Trial. 14 Still, knowledge about outcomes after surgery for LSS in individuals aged 80 and older is limited.…”
mentioning
confidence: 99%
“…The authors found that operative treatment offered a significant benefit over nonoperative treatment in patients who were at least 80 years of age. There were no significant increases in the complication and mortality rates following a surgical procedure in this patient population compared with younger patients 40 .…”
Section: Degenerative Spondylolisthesismentioning
confidence: 58%